Perception of students and insructors on the impacts of gamification on motivation and teamwork among Pharmacy students by using Kahoot! / Nadia Inez Junazli - Nadia Inez, Junazli (2021)
There is an increased used of game-based student response system (GSRS) such as Quizziz and Kahoot! in Malaysian Pharmacy Schools where it has become a tool to increase motivation, engagement and facilitate collaborative learning. Although it is widely used in pharmacy schools across government and private Universities in Malaysia, there is little evidence to understand pharmacy students and their instructor’s perceptions and experiences on using Kahoot! in pharmacy subjects such as pharmaceutics and pharmacology. This qualitative study adopted a phenomenological approach to evaluate students’ and instructors’ experiences through in-depth interview sessions(N=11) to understand their change of attitude, experience, and perception of Kahoot! in terms of motivation and teamwork. This research contributes to the literature by providing an insight into students’ and instructors’ perceived value, usefulness, and overall experience of Kahoot! though qualitative data analysis. The highest influence reported on increased motivation, classroom engagement, teamwork spirit and enhanced learning experience by the students and this is consistent with available literature. Although Kahoot! helped students during revisions and preparing for final examinations, the effect on academic performance was not significant and unknown, The outcome of this study provides an opportunity for gamified educational platforms such as Kahoot to be incorporated as part of the teaching pedagogy to sustain students’ attention, focus, engagement and participation and teamwork spirit in addition to an enjoyable learning experience of pharmacy students in Malaysian Universities.